2020
DOI: 10.1073/pnas.2005019117
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of bacterial RNA polymerase are biomolecular condensates that assemble through liquid–liquid phase separation

Abstract: Once described as mere “bags of enzymes,” bacterial cells are in fact highly organized, with many macromolecules exhibiting nonuniform localization patterns. Yet the physical and biochemical mechanisms that govern this spatial heterogeneity remain largely unknown. Here, we identify liquid–liquid phase separation (LLPS) as a mechanism for organizing clusters of RNA polymerase (RNAP) in Escherichia coli. Using fluorescence imaging, we show that RNAP quickly transitions from a dispersed to clustered localization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(185 citation statements)
references
References 115 publications
(165 reference statements)
8
176
1
Order By: Relevance
“…Given that condensate constituents maintain their ability to diffuse inside the compartment, single-molecule tracking provides a quantitative alternative to FRAP measurements. This method has already been implemented in live C. crescentus and E. coli to investigate PopZ microdomains ( Fig 5C) and RNAP clusters, respectively (23,32). These studies revealed differences between the mobility of molecules inside and outside these compartments.…”
Section: Super-resolution Microscopy As a Tool To Assess Llps In Bactmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that condensate constituents maintain their ability to diffuse inside the compartment, single-molecule tracking provides a quantitative alternative to FRAP measurements. This method has already been implemented in live C. crescentus and E. coli to investigate PopZ microdomains ( Fig 5C) and RNAP clusters, respectively (23,32). These studies revealed differences between the mobility of molecules inside and outside these compartments.…”
Section: Super-resolution Microscopy As a Tool To Assess Llps In Bactmentioning
confidence: 99%
“…For a more in-depth review of BR-body function and phylogenetic distribution, see Muthunayake et al (4). (21) In vitro (18) In vitro (18) In vitro (18) In vitro (22) In vitro (22) In vitro (22) In vitro (47) In vitro (23) In vivo In vitro spherical (23,24,26) In situ icosahedral (95)(96)(97)(98) In situ (25,29) In vitro (23) In vivo (91) In vitro (26) In vitro (23,24,26) ND…”
Section: Current Evidence Demonstrates That Llps May Mediate Subcellumentioning
confidence: 99%
See 3 more Smart Citations